2021
DOI: 10.1109/access.2021.3115024
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students’ Behavior Through User Clustering in Online Learning Settings, Based on Self Organizing Maps Neural Networks

Abstract: An accurate analysis of user behaviour in online learning environments is a useful means of early follow up of students, so that they can be better supported to improve their performance and achieve the expected competences. However, that task becomes challenging due to the massive data that learning management systems store and categorise. With the COVID-19 pandemic still on-going, face-to-face learning settings have migrate into online and blended ones, meaning an increase of online students and teachers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Clustering online learning sets into groups, such as the one in [17], may improve efficiency. Maps (SOMs) and neural networks (SOMNNs) can do this.…”
Section: IImentioning
confidence: 99%
“…Clustering online learning sets into groups, such as the one in [17], may improve efficiency. Maps (SOMs) and neural networks (SOMNNs) can do this.…”
Section: IImentioning
confidence: 99%
“…In terms of predicting student behavior, performance, and learning status, five publications were based on Engineering education [84,[109][110][111][112], one in Social Sciences [113], one in Humanities [114], and two in Sciences [115,116]. Notably, Raza et al [115] designed a time-series predictive model through a long short-term memory network based on information obtained from previous online course interactions and outcomes to predict student progress in the future.…”
Section: Profile and Predictionmentioning
confidence: 99%
“…The Self-Organizing Map method is also used in education to show students [13][14] cognitive structure models and to track learning activities [15]. Many studies using the SOM method have been carried out, such as in previous research named Self-Organizing Map (SOM) Algorithm-Based Applicant Mapping of Predicting Seriousness in Selecting Private University It was found that the SOM method for predicting the interest of private university registrants in 2017 was 0.0065%, in 2018 it was 0.00067%, and in 2019 it was 0.0047% [16], the next research entitled Student modelling using SOM cluster principal component analysis showed that the SOM method for modeling the learning system used the technique of clustering of the student data set using principal, the results were a map of clustering [17] , the next research is entitled the data from the student higher education census: a source of knowledge It was found that the SOM method was used to visualize profiles based on genre and academic status [18], the next research was entitled Using Self-Organizing Maps and Neural Networks, an analysis of student behavior in online learning environments using users clustering to analyze face-to-face systems, online and mixed learning systems obtained face-to-face and online results connected to a methodological approach [19].…”
Section: Introductionmentioning
confidence: 99%